Effects of digital marketing on departmental choice and awareness in higher education - Seong-Won Eum (International Journal of Engineering Business Management)
The purpose of this study is to explore the influence of digital marketing and advertising on students’ perceptions and choices regarding academic departments, employing the social presence theory and the marketing funnel framework. The research sample comprised 156 students specializing in international marketing at B University in Korea, with data analysis performed using Partial Least Squares (PLS) software. This investigation applied a three-stage marketing funnel approach: awareness (impression), consideration (discovery), and conversion(department selection and enrollment).the study identifies that social media marketing, blogs, and SMS marketing are the primary factors affecting students’ departmental selection and admission decisions. Additionally, social media marketing and departmental homepages emerged as crucial in enhancing departmental brand awareness. Conversely, search engine marketing and telemarketing were found to have no significant impact on either department selection or brand awareness. The theoretical contributions of this study demonstrate that implementing digital marketing according to the marketing funnel is effective. In the awareness stage, the use of social media marketing is recommended, while blog marketing is effective during the consideration stage. Finally, in the conversion stage, encouraging clicks on the website and YouTube videos proves to be beneficial. These findings are useful for establishing effective digital marketing strategies and plans for academic departments. Ultimately, this research highlights the impact of digital marketing on department selection and loyalty.